The functioning of the Drosophila CPEB protein Orb is regulated by phosphorylation and requires casein kinase 2 activity. - Li Chin Wong (Public Library of Science (PLoS), 2011)
The Orb CPEB protein regulates translation of localized mRNAs in Drosophila ovaries. While there are multiple hypo- and hyperphosphorylated Orb isoforms in wild type ovaries, most are missing in orb(F303), which has an amino acid substitution in a buried region of the second RRM domain. Using a proteomics approach we identified a candidate Orb kinase, Casein Kinase 2 (CK2). In addition to being associated with Orb in vivo, we show that ck2 is required for orb functioning in gurken signaling and in the autoregulation of orb mRNA localization and translation. Supporting a role for ck2 in Orb phosphorylation, we find that the phosphorylation pattern is altered when ck2 activity is partially compromised. Finally, we show that the Orb hypophosphorylated isoforms are in slowly sedimenting complexes that contain the translational repressor Bruno, while the hyperphosphorylated isoforms assemble into large complexes that co-sediment with polysomes and contain the Wisp poly(A) polymerase.